Students perceptions towards maintenance management and students performance in boarding school / Hasreeq Parapat Muhammad Tamin Parapat - Muhammad Tamin Parapat, Hasreeq Parapat (Faculty Architecture, Planninng and Surveying, 2014)
Good maintenance management ensures the building will be functioning in good condition and required standard. For maintenance management in boarding school, the maintenance management are crucial since the users of building are mostly students. Students in boarding school spend most of their time inside the school compound. The quality of the facilities in the schools can affect the student’s performance in academic. This research is conducted to identify the student’s perception towards maintenance management and students performance in boarding school. To achieve the objectives in this research, researcher are able to produce three objectives which are to investigate maintenance management practice in boarding school, to identify the common problems in boarding school facilities and to investigate students perception towards facilities management and its relation towards students performance. Questionnaires were distributed to the students and interview session was conducted with the school principals or the vice principals in the boarding schools which have knowledge regarding the maintenance management in boarding school. The results from the data analysis shows that maintenance management in the boarding schools can effects the students performance based from the students perceptions.